PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TVS SCS INDONESIA JAKARTA SELATAN - Noviyanti; Ambar Widya Lestari (Journal of Research and Publication Innovation, 2025)
This research aims to examine the influence of leadership style and work discipline on employee performance at PT. TVS SCS Indonesia South Jakarta. The population in this study were all employees of PT. TVS SCS Indonesia South Jakarta and the sample used was a saturated sample with a total of 60 employees. Based on the results of this research, it is concluded that leadership style (X1) has a positive and significant effect on employee performance (Y) with a correlation value of 0.808, meaning it has a strong influence, a coefficient of determination of 65.3%. Hypothesis testing obtained tcount > ttable or (10,440 > 1.672) and this was also strengthened by the  value < sig.0.05 or (0.000 < 0.05). Thus, Ho is rejected and Ha is accepted, so from this research it can be concluded that there is a positive and significant influence between the leadership style variable (X1) on employee performance (Y) at PT. TVS SCS Indonesia. Based on the results of this research, it is concluded that work discipline (X2) has a positive and significant effect on employee performance (Y) with a correlation value of 0.906, meaning it has a strong influence, the coefficient of determination is 82%. Hypothesis testing obtained tcount > ttable or (16.272 > 1.672) and this was also strengthened by the  value < sig.0.05 or (0.000 < 0.05). Thus, Ho is rejected and Ha is accepted, so from this research it can be concluded that there is a positive and significant influence between the work discipline variable (X1) on employee performance (Y) at PT. TVS SCS Indonesia. Based on the results of this research, it is concluded that leadership style (X1) and work discipline (X2) have a positive and significant effect on employee performance (Y) with a correlation value of 0.921, meaning that they have a strong influence. Coefficient of determination 84.9%. Hypothesis testing obtained fcount > ftable or (159.696 > 3.159). Thus, Ho is rejected and Ha is accepted, so from this research it can be concluded that there is a positive and significant influence between the variables leadership style (X1) and work discipline (X2) on employee performance (Y) of PT. TVS SCS Indonesia.